The Impact of Tribal Colleges in the Economic Development of Tribal Communities: A Case Study - Grob, Anne (Current Objectives of Postgraduate American Studies, 2012)
The essay examines a fairly new phenomenon in American Education: Tribal Colleges. As unique institutions of higher learning, established to specifically address educational and cultural needs of American Indians, they play a pivotal role in individual student and tribal community empowerment. It will be illustrated in-depth how one particular Tribal College – Salish Kootenai College – positively impacts and greatly contributes to the economic development of its tribal community.